The role of Si Abdelaziz Salhi in the Algerian revolution in Eastern Hodna Through his notes Personal manuscript - salhi, mouna (The Algerian Historical Journal, 2026)
The Hodna was an important staging area during the Algerian liberation revolution, and there were significant historical events that are still not covered by historians. Because lack of sources, and the Personal Notes of Abdel Aziz Salhi, one of the judges of Hodna during the liberation revolution, are an important historical source that I have relied on to define revolutionary activity in Eastern Hodna. And for the definition of Sheikh Si Abdul Aziz Salhi. The Notes of the Eastern Hodna an important historical period (1958-1959). and it was carefully written about the activities of the political and military leaders of the revolution, and knew their fields of activity, as well as Tasks. which were executed by the judge of the revolution. This study is seen a new cornerstone in the history of the Brood Revolution which needs to be enriched and supported.